Islamic finance and banking system philosophies, principles & practices - Sudin Haron; Nursofiza Wan Azmi Wan (McGraw Hill, 2009)
This book, Islamic Finance and Banking System: Philosophies, Principles & Practices, introduces readers to the history and development of Islamic banking. It provides an in-depth discussion on the theoretical and conceptual aspects of Islamic banking. Key concepts in Islamic finance and banking, and how they are applied to provide alternative Islamic financing options, are examined. The vibrant and thriving takaful industry and Islamic capital market are also explored here. In addition, the book evaluates the role and development of special organizations related to the Islamic financial system.